Insulin-Like Growth Factor 1 Attenuates the Pro-Inflammatory Phenotype of Neutrophils in Myocardial Infarction - Nederlof, Rianne; Reidel, Sophia; Spychala, André; Gödecke, Stefanie; Heinen, André; Lautwein, Tobias; Petzsch, Patrick; Köhrer, Karl; Gödecke, Axel (Frontiers in Immunology, 2022)
Acute myocardial infarction (MI) induces an extensive sterile inflammation, which is dominated in the early phase by invading neutrophils and monocytes/macrophages. The inflammatory response after MI critically affects infarct healing and cardiac remodeling. Therefore, modulation of cardiac inflammation may improve outcome post MI. Insulin-like growth factor 1 (IGF1) treatment reduces infarct size and improves cardiac function after MI via IGF1 receptor mediated signaling in myeloid cells. Our study aimed to investigate the effect of IGF1 on neutrophil phenotype both in vitro and in vivo after MI. We show that IGF1, induces an anti-inflammatory phenotype in bone marrow derived neutrophils. On the molecular and functional level IGF1 treated neutrophils were indistinguishable from those induced by IL4. Surprisingly, insulin, even though it is highly similar to IGF1 did not create anti-inflammatory neutrophils. Notably, the IGF1 effect was independent of the canonical Ras/Raf/ERK or PI3K/AKT pathway, but depended on activation of the JAK2/STAT6 pathway, which was not activated by insulin treatment. Single cell sequencing analysis 3 days after MI also showed that 3 day IGF1 treatment caused a downregulation of pro-inflammatory genes and upstream regulators in most neutrophil and many macrophage cell clusters whereas anti-inflammatory genes and upstream regulators were upregulated. Thus, IGF1 acts like an anti-inflammatory cytokine on myeloid cells in vitro and attenuates the pro-inflammatory phenotype of neutrophils and macrophages in vivo after MI. IGF1 treatment might therefore represent an effective immune modulatory therapy to improve the outcome after MI.